The influence of television on the food habits of schoolchildren and its association with dental caries - Regina de Nazaré Marreiros Tavares Silva; Danilo Antonio Duarte; Arlete Maria Gomes deOliveira (Wiley, 2020)
Abstract Objectives The consumption of food with a high‐sugar content is encouraged by the food industry through television (TV) aimed at children and may be associated with dental caries. This study aims to evaluate the influence of TV on the food habits of schoolchildren aged years and its association with dental caries. Material and methods This was an observational, epidemiological, and cross‐sectional study. Five neighborhoods of Belem District were selected, and then two schools from each neighborhood were drawn (one private and one public). All sixth and seventh grade students were selected. Data were extracted from questionnaires completed by schoolchildren and their parents and the decayed, missing, and filled teeth (DMFT/dmft) indices of the schoolchildren. The indices were carried out by three examiners previously calibrated (κ > .80). Logistic regression analysis was performed to investigate the association of variables of study with consumption of cariogenic foods and occurrence of dental caries. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. Results Schoolchildren who watched TV for >90 min were more likely to consume cariogenic foods (OR = 2.38; 95% CI [1.57, 3.60]) and have a DMFT + dmft >1 (OR = 2.10; 95% CI [1.37, 3.26]). Those who consumed cariogenic foods while watching TV were more likely to have DMFT + dmft >1 (OR = 14.75; 95% CI [8.24, 6.40]). Parents who bought foods they saw on TV contributed to a higher consumption of cariogenic foods (OR = 3.29; 95% CI [2.07, 5.24]) and DMFT + dmft >1 (OR = 3.93; 95% CI [2.09, 7.37]) among their children. Conclusions TV can influence the eating habits of schoolchildren aged 10 to 12 and the food purchases of their parents, stimulating the consumption of cariogenic foods and contributing to the development of dental caries.